Retrofitting earthquake-damaged RC structural walls with openings by externally bonded FRP strips and sheets - Li, Bing (2014)
The majority of research studies on the behavior of reinforced concrete members with externally bonded fiber reinforced polymer (FRP) sheets have been focused on beams, columns, and beam-column joints. However, limited experimental studies have been conducted to investigate the performance of structural walls retrofitted by wrapping FRP strips or sheets, especially on structural walls with openings. The validated retrofitting schemes for strengthening damaged walls without openings may not be suitable for walls with openings. Therefore, a series of experimental studies were carried out at Nanyang Technological University, Singapore, to study the effectiveness of the proposed repair and strengthening schemes in recovering the seismic performance of the damaged walls with irregular or regularly distributed openings. The strut-and-tie approach was utilized to design the repair schemes. The repaired walls managed to recover their strength, dissipated energy, and stiffness reasonably, indicating that the strut-and-tie approach can be a good design tool for FRP-strengthening of structural walls with openings. Moreover, the shear and sliding capacities of repaired walls were enhanced by using fiber anchors. The repaired walls failed primarily because of debonding of the fiber reinforced polymer at the base of the walls.